Measurement of multiplicity and momentum spectra in the current and target regions of the Breit frame in deep inelastic scattering at HERA - Breitweg, J; Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Repond, J; Stanek, R; Yoshida, R; Mattingly, M; Abbiendi, G; Anselmo, F; et al. (1999)
Charged particle production in neutral current deep inelastic scattering (DIS) has been studied using the ZEUS detector. The evolution of the mean multiplicities, scaled momenta and transverse momenta in Q2 and cursive Greek chi for 10 < Q2 < 5120 GeV2 and cursive Greek chi > 6 × 10-4 has been investigated in the current and target fragmentation regions of the Breit frame. Distributions in the target region, using HERA data for the first time, are compared to distributions in the current region. Predictions based on MLLA and LPHD are inconsistent with the data.